Research on the Application of Big Data Technology in Artificial Intelligence - Lin, Jie (Journal of Artificial Intelligence and Information, 2025)
With the rapid development of network information technology, human society is entering an era of information explosion, which has created unprecedented convenience for the public to access diverse and in-depth information resources. Behind this transformation, it is inseparable from the deep integration and mutual promotion of big data technology and artificial intelligence, which together constitute the key technological guarantee to support people's efficient and accurate access to information resources. This article delves into the unique advantages of big data and artificial intelligence technology, revealing how their combination can reshape the landscape of the information age. Analyzed its core types, including but not limited to distributed storage technology, data mining algorithms, and real-time data processing capabilities, which provide a solid foundation for the collection, organization, and analysis of massive data. The widespread application of big data in the field of artificial intelligence, such as optimizing prediction models through machine learning algorithms and improving image recognition accuracy through deep learning techniques, not only greatly enriches the functional boundaries of artificial intelligence, but also promotes its innovative practices in multiple fields such as healthcare, smart cities, and financial technology. The work of this article is not only a comprehensive examination of the current status of big data and artificial intelligence technology, but also a forward-looking exploration of future development trends. With the continuous advancement of technology, the deep integration of big data and artificial intelligence will continue to deepen, opening up broader space for the future development of artificial intelligence and having immeasurable value in promoting social progress and improving the quality of life.